Meta-analysis of the effect of non-pharmacological interventions on the development of dysgeusia in patients undergoing radiotherapy for head and neck squamous cell carcinoma - Yuyang Li; Lili Hou; Xing Gan; Xi Yang (Scientific Reports)
Abstract This study was conducted by searching electronic databases from January 1, 2000 to August 8, 2023: Web of Science, PubMed, Cochrane Library, Embase, Scopus, Google Scholar, China Biomedical Literature Database (CBM), China National Knowledge Network (CNKI), China Science and Technology Journal Database (VIP) and Wan-fang Database were included in 14 studies with a total sample size of 1630 cases. This study conducted a meta-analysis of the literature published in recent years on the occurrence of dysgeusia in Head and neck squamous cell carcinoma (HNSCC) patients with non-pharmacological treatment, in order to provide the latest evidence-based evidence for medical staff and provide a basis for further intervention of dysgeusia in HNSCC patients. Compared with conventional care in the control group, In the experimental group, the non-pharmacological intervention reduced the score of dysgeusia [MD = − 0.76, 95% CI (− 1.04, − 0.48), P < 0.00001] and the incidence of dysgeusia [MD = 0.17, 95% CI (0.09, 0.31), P < 0.00001].